Perceptions on causes of poor academic performance amongst selected secondary schools in Kericho sub - county. - Rono, Kenneth Kiplangat. (JOOUST, 2014)
The purpose of this study was to determine perceptions of causes of poor academic performance in secondary schools amongst selected secondary schools in Kericho sub-county. Specifically the study; was to; determine perceptions on causes of poor academic performance in secondary schools in Kericho sub-county, examine perceptions concerning the perceptions concerning the relationship between family background and students' poor academic performance in Kericho sub-county examine perceptions concerning the relationship between socio-economic status and academic achievements of students in Kericho sub-county and to examine perceptions concerning school factors influencing students' academic performance in Kericho sub-county. The study was done by developing conceptual framework in relation to perceptions on causes of poor academic performance in secondary schools in school. Selected literature revealed that the major highlights on causes of poor academic performance are; perceptions, family background, socio-economic status and school factors. However, there is need to find out what other factors are causing poor academic performances among students and the extent of these causes. A descriptive survey design was used. Data was collected from 21 secondary schools and a total of 38 respondents including students, teachers and parents were contacted. Data was analyzed using SPSS with use of frequencies, percentages and mean ratings. It was discovered that the perception of parents, teachers and students was not any different as was reflected in the frequencies and percentages. The study found out that majority of respondents agreed that perceptions are key to a students' poor performance amongst other factors especially social economic. The study recommended that there is a• strong need for sensitization, Career guidance and having extra time for the students. The study suggested areas of further research on social economic factors and sources of perceptions of respondents .The study was expected to give insight reference to policy makers, scholars and researchers in order to improve the weak areas.
Keywords: Causes of poor academic performance.; causes of poor academic performance amongst selected secondary schools in Kericho sub - county.; Kenya.